A Presentation of Massive Hemoptysis in a Patient with Churg-Strauss Syndrome - Fadi Hikmat; David B Pearse; Mahendra Damarla (Canadian Respiratory Journal)
Given that Churg-Strauss syndrome is a systemic small-vessel vasculitis, it is not usually considered in patients who present with massive hemoptysis, which is typically caused by bronchiectasis, cancer or, in some cases, aberrant bronchial arteries. This article, however, describes a novel case involving a 50-year-old Churg-Strauss patient who presented with sudden-onset massive hemoptysis. Details of the physical examination, laboratory investigations and several imaging studies, including computed tomography, bronchoscopy and three-dimensional imaging, are presented.